2006
DOI: 10.1016/j.jcrs.2005.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Topographic screening of donor eyes for previous refractive surgery

Abstract: The results led to a proposed criteria-based system using Orbscan corneal topography to screen eye-bank eyes for previous refractive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have investigated the role of elevation topography to: (i) establish normal patterns and standards 45,46 , (ii) identify high-risk individuals who may experience corneal ectasia after LASIK 18,27 , (iii) screen eye-bank eyes for previous refractive surgery 47 , (iv) evaluate possible changes in posterior corneal elevation after laser in situ keratomileusis (LASIK) or photorefractive keratectomy (PRK) 48 , and (v) build population-based average three dimensional (3-D) atlases or standards of the human cornea 49 . Different patterns have been proposed to describe aspects of elevation topography maps including: “island”, “regular ridge”, “irregular ridge”, “incomplete ridge”, and “unclassified” 50-52 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the role of elevation topography to: (i) establish normal patterns and standards 45,46 , (ii) identify high-risk individuals who may experience corneal ectasia after LASIK 18,27 , (iii) screen eye-bank eyes for previous refractive surgery 47 , (iv) evaluate possible changes in posterior corneal elevation after laser in situ keratomileusis (LASIK) or photorefractive keratectomy (PRK) 48 , and (v) build population-based average three dimensional (3-D) atlases or standards of the human cornea 49 . Different patterns have been proposed to describe aspects of elevation topography maps including: “island”, “regular ridge”, “irregular ridge”, “incomplete ridge”, and “unclassified” 50-52 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether eye banks should accept corneas that have had previous PRK with adjuvant mitomycin-C for donation is unknown; some studies have indicated no effect of PRK with mitomycin-C on the endothelium 37-39 whereas other studies have found detrimental effects, including increased endothelial cell loss. 40-42 However, determining which potential donor corneas have had PRK is a challenge for eye banks, 43-45 and determining which corneas also received adjuvant mitomycin-C will be more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of these techniques increases the cost of tissue preparation, and each method has its own sensitivity and specificity. 1,[5][6][7] Additionally, the reliability of the proposed methods could be reduced by postmortem tissue changes. 8 To the best of our knowledge, this is the first case of PK that necessitated rekeratoplasty due to poor postoperative refractive status of the eye.…”
Section: Discussionmentioning
confidence: 99%